HUBUNGAN ANTARA PENGETAHUAN DAN PERILAKU GIZI SEIMBANG DENGAN STATUS GIZI PADA REMAJA DI WILAYAH KABUPATEN TANGERANG TAHUN 2021 - Inggit Sekar Rayipratiwi; Leni Sri Rahayu; Fitria Fitria (ARGIPA (Arsip Gizi dan Pangan), 2022)
Nutritional status is the nutritional state of a person due to nutrients that enter and leave so that they can find out whether they have normal or problematic nutrition (malnutrition). Nutritional problems are defined are stunting, wasting, and obesity as well as deficiencies of micronutrients such as anemia. Nutritional status can be influenced by several factors. Among the factors that influence nutritional status are knowledge and behavior of balanced nutrition. This study aimed to determine the relationship between knowledge and behavior of balanced nutrition with the nutritional status of adolescents in the Tangerang Regency in 2021. This research is a quantitative study with a cross-sectional research design with a total sample of 110 people obtained from the purposive sampling method. A knowledge and behavior of balanced nutrition variables using a questionnaire. The results showed that there was a significant relationship between balanced nutritional behavior and adolescent nutritional status and there was no relationship between nutritional knowledge and adolescent nutritional status, so it is expected that adolescents in the Tangerang District in 2021 to improve balanced nutritional behavior such as eating a variety of foods, regularly consuming vegetables and fruits, as well as using digital media to find out what to pay attention to in measuring weight and height, as well as how to calculate the nutritional status of adolescents.